Analisis Solusi Permasalahan Zakat Produktif - Khusnul Fauziah; Naufal Kurniawan (Politeknik Baubau, 2023)
Philanthropy is generosity, generosity, social contribution or something that shows love for humans. Philanthropy is an alternative that is used to reduce social inequality, create life benefits and improve people's welfare, such as through the empowerment of productive endowments. However, currently in Banjarnegara not many waqf are managed productively. This study aims to analyze the problems of productive waqf and their solutions in Banjarnegara Regency. The method used is descriptive method, while data collection is done by examining and exploring data sources or other information relevant to the study. The results obtained explain that the problems causing waqf management in Banjarnegara Regency are not optimal and the solution is divided into three aspects, namely human resource aspects, institutional aspects and government aspects. The aspects of human resource problems have the greatest influence compared to other aspects. The solutions that most affect the level of management of waqf assets are outreach and education to the public, increasing coordination with other related institutions and waive the cost of certifying waqf land.